Equivolumetric Evolution of Planar Curves - Hwan Pyo Moon (Abstract and Applied Analysis)
We present the equivolumetric evolution of planar curves, which is a new type of curvature dependent evolution for a flame propagation model. This evolution reflects the nonlinear contribution of the curvature of the front to the flame propagation speed. We also present some numerical results of the equivolumetric evolution using the level set method.